Relevance of chronic stress and the two faces of microglia in Parkinson’s disease - Herrera, Antonio J.; Espinosa-Oliva, Ana M.; Carrillo-Jiménez, Alejandro; Oliva-Martín, María J.; García-Revilla, Juan; García-Quintanilla, Alberto; de Pablos, Rocío M.; Venero, José L. (Frontiers in Cellular Neuroscience, 2015)
This review is aimed to highlight the importance of stress and glucocorticoids (GCs) in modulating the inflammatory response of brain microglia and hence its potential involvement in Parkinson’s disease (PD). The role of inflammation in PD has been reviewed extensively in the literature and it is supposed to play a key role in the course of the disease. Historically, GCs have been strongly associated as anti-inflammatory hormones. However, accumulating evidence from the peripheral and central nervous system have clearly revealed that, under specific conditions, GCs may promote brain inflammation including pro-inflammatory activation of microglia. We have summarized relevant data linking PD, neuroinflamamation and chronic stress. The timing and duration of stress response may be critical for delineating an immune response in the brain thus probably explain the dual role of GCs and/or chronic stress in different animal models of PD.